IMPLEMENTATION OF SUPPORT GROUPS AS AN EFFORT TO IMPROVE THERAPY ADHERENCE AND BLOOD SUGAR CONTROL OF PATIENTS WITH DIABETES MELLITUS IN KEDUNG TARUKAN, TAMBAKSARI SUB-DISTRICT SURABAYA - Aryani, Toetik; Budiatin, Aniek Setiya; Izza, Zamrotul; Hikmawati, Dyah; Mazidda, Sakinato (Caring: Jurnal Pengabdian Masyarakat, 2025)
Abstract Diabetes mellitus is a chronic metabolic disease characterized by elevated blood glucose levels, which over time can cause damage to the heart, blood vessels, eyes, kidneys and nerves. The purpose of this service is to provide health education about diabetes mellitus for the Kedung Tarukan community. Tambaksari sub-district, Surabaya. This service activity is carried out through observation and direct counseling methods to PKK members and local residents. The results show that counseling can increase the knowledge of each individual, pre test 46% and post test 76%.